Enhancement of basophil chemotaxis in vitro by virus-induced interferon. - Lett-Brown, M A (1981)
It is well established that viral infections may precipitate or worsen attacks of bronchial asthma. Furthermore, in symptomatic atopic subjects, the local accumulation of basophils and the production of a basophil chemotactic factor have been reported. We have investigated the effect of cell-free supernates from viral stimulated cultures of human mononuclear cells on the in vitro migration of human basophils. Our results show the presence of a factor in these culture supernates that enhances the migration of basophils toward two separate chemoattractants, a peptide from C5 and a lymphokine. The enhancing activity, while affecting basophil migration, did not change the response of monocytes. The enhancing activity resembled viral-induced interferon when (a) pH 2 stability, (b) heat resistance, (c) trypsin sensitivity, and (d) species-specificity were compared. Finally, the enhancing activity for basophil chemotaxis and the interferon titer were highly correlated in preparations with a 10(4)-fold difference in interferon specific activity. Our studies show that viral-induced interferon can augment the in vitro chemotactic response of basophils. Because mediators present in basophils may be involved in the pathogenesis of immediate hypersensitivity, the modulation of basophil movement by interferon suggests a possible mechanism for the association between viral infections and atopic disorders.